PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN DIGITAL BERBASIS EDUCAPLAY BERBANTUAN RIDDLE GAME PADA PELAJARAN PENDIDIKAN PANCASILA TERHADAP HASIL BELAJAR KOGNITIF SISWA KELAS II DI SDN KADEMANGAN 2 KOTA PROBOLINGGO - Adella Pramesti Ekaditya Rohman; Didit Yulian Kasdriyanto; Ryzca Siti Qomariyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was conducted due to the lack of use of digital learning media so that students' understanding of the Pancasila Education subject matter is still low, causing students' cognitive learning outcomes to be low. The aim of this research is to improve students' cognitive learning outcomes through the use of educaplay-based digital learning media assisted by riddle games in class II Pancasila Education subjects at SDN Kademangan 2, Probolinggo City. The method used in this research is a quantitative method with a one group pretest-posttest design. In this research, two measurements were carried out, namely giving a pretest before treatment and a posttest after treatment. Before giving the pretest and posttest, a test instrument test is carried out first which includes a validity test, reliability test, question discrimination test, and question difficulty level test. Based on the research results, the results obtained were that there was a significant increase in students' cognitive learning outcomes which can be seen from the average difference between the pretest and posttest of 19.22. The paired sample t-test produces a sig value. (2-tailed) is 0.000 where the value is smaller than 0.05 (0.000 < 0.05) which can be said that H0 is rejected and H1 is accepted.The results of the research show that Educaplay-based digital learning media assisted by Riddle Game in Pancasila Education lessons, the material on recognizing Pancasila symbols, has a significant effect on the cognitive learning outcomes of class II students at SDN Kademangan 2, Probolinggo City.